2001
DOI: 10.1093/hmg/10.18.1945
|View full text |Cite
|
Sign up to set email alerts
|

Telomere maintenance by telomerase and by recombination can coexist in human cells

Abstract: Immortal human cells maintain their telomeres by two independent mechanisms, a prevalent one dependent on de novo synthesis of telomeric DNA by telomerase, and a rarer one based on telomere recombination [alternative lengthening of telomeres (ALT)]. Studies with yeast have indicated that expression of telomerase inhibits telomere recombination. In the present study, we have investigated whether expression of telomerase in cells that use ALT would similarly reveal dominance of telomere elongation by telomerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 37 publications
6
116
0
6
Order By: Relevance
“…No AdhTERTp-E1A-mediated cytotoxicity was detected in these WI38-VA13 tumor cells, in which telomere maintenance has been attributed to the ''ALT'' pathway. 38 Taken together, these data suggest that AdhTERTp-E1A oncolytic virus-mediated cytolysis is largely restricted to human tumor cells that are positive for telomerase expression.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…No AdhTERTp-E1A-mediated cytotoxicity was detected in these WI38-VA13 tumor cells, in which telomere maintenance has been attributed to the ''ALT'' pathway. 38 Taken together, these data suggest that AdhTERTp-E1A oncolytic virus-mediated cytolysis is largely restricted to human tumor cells that are positive for telomerase expression.…”
Section: Resultsmentioning
confidence: 73%
“…Virtually no cytotoxicity was detected with either of the normal cell lines tested (Fig 1d). To further confirm that AdhTERTp-E1A-mediated cytotoxicity to tumor cells was directly linked to their hTERT expression, a telomerase negative SV-40 large T antigen transformed cell line, WI38-VA13, 38 was subjected to AdhTERTp-E1A virus infection and subjected to MTS assay for determining cell viability (Fig 1e). No AdhTERTp-E1A-mediated cytotoxicity was detected in these WI38-VA13 tumor cells, in which telomere maintenance has been attributed to the ''ALT'' pathway.…”
Section: Resultsmentioning
confidence: 95%
“…To this end, we ectopically expressed both subunits of telomerase in U2OS osteosarcoma ALT cells. Earlier studies reported distinct outcomes after telomerase introduction into ALT SV40T-immortalized fibroblasts: either ALT was preserved and T-SCEs were unaffected (Cerone et al, 2001) or ALT was abolished and T-SCE frequency was reduced (Ford et al, 2001;Bechter et al, 2004). These apparent discrepancies may possibly be due to distinct telomerase levels in the cells (Henson et al, 2002).…”
Section: Ectopic Expression Of Telomerase In Alt Cancer Cells Reducesmentioning
confidence: 99%
“…The VA13 subtype was created with SV40 transformation, which inactivates the tumor suppressors p53 and Rb (Tokutake et al, 1998), and alters signal transduction pathways regulated by the phosphatase family of PP2A. The recombinant expression replacement of TERT and TER in this cell line does not result in the loss of ALT phenotypes, indicating that ALT and telomerase-dependent telomere maintenance can coexist (Cerone et al, 2001). As telomere length maintenance can be completely uncoupled from telomerase action in ALT cells, we can specifically test the growth-promoting functions of telomerase and compare them with the parental isogenic VA13 cell controls expressing empty retroviral vector.…”
Section: Introductionmentioning
confidence: 99%